Gene polymorphisms of superoxide dismutases and catalase in diabetes mellitus - Lacinova Zdena; Hilgertova Jirina; Skrha Jan; Flekac Milan; Jarolimkova Marcela (BMC, 2008)
Abstract Background Reactive oxygen species generated by hyperglycaemia modify structure and function of lipids, proteins and other molecules taking part in chronic vascular changes in diabetes mellitus (DM). Low activity of scavenger enzymes has been observed in patients with DM. Protective role of scavenger enzymes may be deteriorated by oxidative stress. This study was undertaken to investigate the association between gene polymorphisms of selected antioxidant enzymes and vascular complications of DM. Results Significant differences in allele and genotype distribution among T1DM, T2DM and control persons were found in SOD1 and SOD2 genes but not in CAT gene (p < 0,01). Serum SOD activity was significantly decreased in T1DM and T2DM subjects compared to the control subjects (p < 0,05). SOD1 and SOD2 polymorphisms may affect SOD activity. Serum SOD activity was higher in CC than in TT genotype of SOD2 gene (p < 0,05) and higher in AA than in CC genotype of SOD1 gene (p < 0,05). Better diabetes control was found in patients with CC than with TT genotype of SOD2 gene. Significantly different allele and genotype frequencies of SOD2 gene polymorphism were found among diabetic patients with macroangiopathy and those without it. No difference was associated with microangiopathy in all studied genes. Conclusion The results of our study demonstrate that oxidative stress in DM can be accelerated not only due to increased production of ROS caused by hyperglycaemia but also by reduced ability of antioxidant defense system caused at least partly by SNPs of some scavenger enzymes.